Strategi dalam Pengembangan Pembelajaran Berdiferensiasi Biologi di SMA Al Hikmah Sirampog: Tantangan dan Solusi - Riska Dwi Wulansari; Atika Okta Melisa; Shofwatun Nada (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
This research focuses on differentiated learning in biology subjects at SMAS Al Hikmah, which emphasizes the unique characteristics of each student. However, there are various obstacles in its implementation. The purpose of this study is to analyze the strategies used by biology teachers, the challenges faced, and the solutions applied in overcoming these problems. The research method used is qualitative descriptive, with data collection through interviews and documentation. The research sample consisted of Biology Teachers at SMAS Al Hikmah Sirampog. In practice, differentiated learning faces a number of challenges, including time constraints that force teachers to be more careful in planning the time for each material to be taught. In addition, teachers have difficulty in implementing content differentiation because the majority of students (90%) are students who are not allowed to use mobile phones. To overcome these obstacles, teachers are advised to develop a lesson plan that includes teaching strategies, learning media, and learning procedures. This aims to maximize time during the teaching and learning process in the classroom. In addition, teachers can replace content differentiation with activities related to P5 (Pancasila student profile strengthening project), such as making videos or podcasts, to minimize time limitations.